2020
DOI: 10.1097/jom.0000000000002130
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Mobile Health Management Program With a Challenge Strategy for Improving the Cardiovascular Health of Workers

Abstract: Background: Workers’ cardiovascular health can be influenced by individual willingness to practice healthy behaviors. A mobile health management program with a challenge strategy was administered to promote workers’ healthy behaviors among small to medium-sized enterprises. Methods: A 12-week program consisted of health communication with a challenge strategy was administered to the workers. Results: The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A previous review concluded that mHealth interventions are potentially effective and feasible for increasing PA in the workplace [ 33 ], with some evidence of short-term weight loss [ 34 ]. In contrast, other studies reported nonsignificant changes in PA level [ 35 ] and weight control [ 7 , 24 ] in certain groups of workers.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…A previous review concluded that mHealth interventions are potentially effective and feasible for increasing PA in the workplace [ 33 ], with some evidence of short-term weight loss [ 34 ]. In contrast, other studies reported nonsignificant changes in PA level [ 35 ] and weight control [ 7 , 24 ] in certain groups of workers.…”
Section: Introductionmentioning
confidence: 81%
“…Thus, the World Health Organization provides a global action plan and framework for practical and feasible policy actions to support, maintain, and increase PA [ 6 ]. Establishing and maintaining healthy lifestyles in the adult population is essential [ 7 ], and it should be noted that most of the adult population are workers [ 8 ]. Inadequate PA is identified as a significant problem in adult worker groups [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chronic diseases is rising rapidly, the number of patients is increasing, and medical costs are rising sharply. People's health needs are growing, and medical resources in China are severely inadequate and unevenly distributed [7].…”
Section: Introductionmentioning
confidence: 99%